The Impact of SDG 30 on Eco-Literacy and Green Purchase Maqashid Syariah Perspective - Laila Ifti Faiyah; Nur Azizah Hasanah; Mardhiyah Hayati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the impact of Sustainable Development Goals (SDGs) 2030 on eco-literacy and green purchase behaviour from the perspective of Maqashid Syariah. Climate change and the need for sustainability highlight the importance of eco-literacy in fostering consumer environmental awareness. This research employs a quantitative method using a survey of 96 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The findings indicate that eco-literacy significantly influences the brand image and green product knowledge. These variables mediate the relationship between eco-literacy and green purchase behaviour. The results emphasize that consumers with higher levels of eco-literacy tend to prefer sustainable brands and environmentally friendly products. From the perspective of maqashid syariah, these findings align with the principles of hifz al-'aql (protection of intellect) and hifz al-maal (protection of wealth).